Association between landscape heritage elements and place attachment among visitors in Taiping Lake Garden - Abd Gani, Nurul Hijrah; Mohamed, Noorizan; Ujang, Norsidah (Universiti Malaysia Kelantan Press, 2015)
Various researches have been conducted by researchers on landscape heritage and place attachment. The researches were done in isolation according to the differing field of study. It is noticed that there still a gap of knowledge on the association between landscape heritage elements and place attachment. As commonly realized by most of people, the priceless heritage is susceptible to deteriorate or destroyed by either natural phenomenon or human negligence. Henceforth, creating public awareness on this irreplaceable heritage is a necessity to ensure its continuous existence in the future. This paper aims to document the landscape heritage elements and examine their influence on visitors' attachment to Taiping Lake Garden. Taiping Lake Garden was selected as the study site as it is one of the oldest gardens in Malaysia. The method employed in the study is managed through archival study and observation for documenting the heritage elements found in Taiping Lake Garden. Meanwhile, survey method is used to explore the influence of heritage elements on visitors' attachment to Taiping Lake Garden. The results indicate that physical, non-physical and natural landscape as the landscape heritage elements of Taiping Lake Garden. While, the result of the surveys demonstrated that these heritage elements influence the visitors' attachment to the place. From the study, indicates that more effort needs to be done in promoting the landscape heritage of Taiping Lake Garden to sustain its existence in the future.